Fib model code for concrete structures 2010 - Fédération internationale du béton (Lausanne, Switzerland : Ernst & Sohn, a Wiley brand, 2013)
The International Federation for Structural Concrete (fib) is a pre-normative organization. 'Pre-normative' implies pioneering work in codification. This work has now been realized with the fib Model Code 2010. The objectives of the fib Model Code 2010 are to serve as a basis for future codes for concrete structures, and present new developments with regard to concrete structures, structural materials and new ideas in order to achieve optimum behaviour. The fib Model Code 2010 is now the most comprehensive code on concrete structures, including their complete life cycle: con.
4.5.2.2 Ultimate limit states; 4.5.2.3 Fatigue verification; 4.5.2.4 Verification of structures subjected to impact and explosion; 4.5.2.5 Serviceability limit states; 4.6 Global resistance format; 4.6.1 General; 4.6.2 Basic rules for global resistance approach; 4.6.2.1 Representative variables; 4.6.2.2 Design condition; 4.7 Deemed-to-satisfy approach; 4.7.1 General; 4.7.2 Durability related exposure categories; 4.8 Design by avoidance; 5 Materials; 5.1 Concrete; 5.1.1 General and range of applicability; 5.1.2 Classification by strength; 5.1.3 Classification by density.
Includes index.
Online resource; title from PDF title page (Wiley, viewed November 13, 2013).
5.1.4 Compressive strength.
Keywords: Concrete -- Cracking; Concrete construction; Strains and stresses; TECHNOLOGY & ENGINEERING -- Civil -- General; Concrete construction; Concrete -- Cracking; Strains and stresses; Electronic books; Electronic books